Implementasi Social Media Marketing pada Bayu Gatra Sports - Dwi Alfito Ferdiansyah (Fakultas Ilmu Sosial dan Ilmu Politik, 2024)
Bayu Gatra Sports is a sports equipment retail business founded by Bayu Gatra Sanggiawan in 2020. This business actively utilizes social media as a marketing tool. This study aims to analyze the implementation of social media marketing at Bayu Gatra Sports. This study uses a descriptive qualitative approach with data collection through interviews, observations, and documentation. The results of the study show that Bayu Gatra Sports implements social media marketing through Instagram, TikTok, and WhatsApp, based on four main dimensions, namely the context dimension involves creating relevant content regularly. The communication dimension reflects active two-way interaction between the business and its audience. The collaboration dimension includes collaboration with footballers, local sports communities, and content created by customers. The connection dimension highlights efforts to maintain long-term relationships with customers. The results of this study illustrate how the implementation of social media marketing supports audience engagement and customer loyalty at Bayu Gatra Sports.
Reaploud Repository April 2026
Keywords: Social Media Marketing; Implementation; Digital Marketing